1998
DOI: 10.1021/bi981114e
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of the Core and Peripheral Light-Harvesting Complexes of Rhodospirillum molischianum from Separately Isolated Components

Abstract: In most purple bacteria, the core light-harvesting complex (LH1) differs from the peripheral light-harvesting complex (LH2) in spectral properties and amino acid sequences. In Rhodospirillum (Rs. )molischianum, however, the LH2 closely resembles the LH1 of many species in amino acid sequence identity and in some spectral properties (e.g., circular dichroism and resonance Raman). Despite these similarities to LH1, the LH2 of Rs. molischianum displays an absorption spectrum similar to the LH2 complexes of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…It has been proposed that the transmembrane helix domains of the ␣-polypeptides show a low level of sequence conservation when different proteobacteria are compared; the one exception is His31. The major determinant for the specific Bchl-B850 geometry may be found predominantly in the residues outside the transmembrane region (3, 7,32,36,43). It has been found that insertion of four residues (TTWA) towards the carboxy terminus of the transmembrane helix of the ␣-apoprotein leads to the absence of LH2 complexes (3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the transmembrane helix domains of the ␣-polypeptides show a low level of sequence conservation when different proteobacteria are compared; the one exception is His31. The major determinant for the specific Bchl-B850 geometry may be found predominantly in the residues outside the transmembrane region (3, 7,32,36,43). It has been found that insertion of four residues (TTWA) towards the carboxy terminus of the transmembrane helix of the ␣-apoprotein leads to the absence of LH2 complexes (3).…”
Section: Discussionmentioning
confidence: 99%
“…This difference is borne out by the facts that LH1 can be readily dissembled into individual ␣ 1 ␤ 1 Bchl 2 units, often termed B820 (33), and that it can also be fractionated into a series of LH1 oligomers that vary in size from (␣␤) 2-3 to (␣␤) 10 -11 (34,35). Neither of these types of subdivision of a nonameric LH2 complex has been reported, although the octomeric LH2 of Rhodospirillum molischianum has been successfully dissociated into B820 subunits (36). Fig.…”
Section: Structural Basis For Variations In Size and Shape Of The Lh1mentioning
confidence: 99%
“…Reconstitution assays [23] show that in many cases light harvesting complexes with very similar optical properties to the wild-type complexes can be reconstituted in vitro from their individual components [24,25]. Truncated versions of natural proteins, chemically synthesized de novo proteins, and mutagenetic gene products have been studied, revealing residues essential to formation of αβ-subunits and full complexes [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%